رواداری کی معاشرتی اہمیت اور تقاضے سیرتِ نبویﷺ کی روشنی میں تجزیاتی مطالعہ: The Social Importance and Requirements of Tolerance Analytical Study in the Light of the Prophet's (PBUH) Life - Dr. Abbas Ali Raza; Hafiza Urwa Ismail; Dr. Qazi Abdul Manan (Al Manhal Research Journal, 2023)
Tolerance is one of the highest moral values, which are essential for the survival of the society and its stability. Without tolerance, peace and tranquility disappear from the society. Like other religions of the world, Islam also demands tolerance from its followers. Islamic society can achieve rise and development. The entire life of the Holy Prophet (PBUH) is an excellent and shining example of tolerance. He (peace be upon him) forgave even his mortal enemies. Today we need again to make use of good character and remember this forgotten lesson of tolerance so that again such a bright morning will dawn that will make our lives happy.